Firm innovation and covenant tightness - Ma, Zhiming; Novoselov, Kirill E.; Stice, Derrald; Zhang, Yue (Review of Accounting Studies, 2024)
Abstract This study explores the association between firm innovation and loan covenant strictness. We find that lenders construct stricter contracts for firms filing more patents, consistent with lenders imposing more oversight on firms when they enter the commercialization stage after having demonstrated their inventiveness. Our results hold under propensity score matching and entropy balancing, and when exploiting the American Inventors Protection Act as a shock affecting unrelated banks’ access to patent filing information. The relationship we document is stronger when the lender has more expertise and for firms with higher default risk. We demonstrate that borrowers’ patent filings are associated with more future R&D and capital investment and with a higher likelihood of their acquiring firms in the industry of their patent filings. Our results are consistent with the theoretical prediction that lenders interpret patent filings as indicative of high inventive potential that requires stricter discipline and oversight by lenders in order to be converted into actual business success, and with them designing debt contract terms accordingly.